Impaired visual sensitivity within the ipsilesional hemifield following parietal lobe damage - Snow, J; Miranda, R; Humphreys, G (2013)
The parietal cortex is considered to be part of a network of brain areas that modulates competitive interactions between targets and irrelevant distracters in early visual cortex, however there is currently little causal evidence to support this in human observers. It is also unclear as to whether parietal influences on visual perception in humans are limited to the contralesional hemispace or whether a unilateral lesion affects visual sensitivity bilaterally. Here we examined visual sensitivity in two patients with spatial neglect and extinction arising primarily from left-parietal damage. We used a sensitive psychophysical task based on those previously used to demonstrate loss of stimulus selection after lesions to extrastriate cortex. Observers discriminated the orientation of a lateralized suprathreshold target grating that appeared alone or in the context of nearby salient disc distracters. For parietal patients, target sensitivity within both the contralesional and ipsilesional fields was compromised by the presence of distracters. Conversely, healthy matched controls were unaffected by distracters. These results indicate that parietal cortex damage can influence visual perception within both the ipsi- as well as the contralesional field. © 2011 Elsevier Ltd.